2020
DOI: 10.3390/agronomy10040457
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Local Peach (Prunus persica) Accessions from La Palma Island (Canary Islands, Spain)

Abstract: Peach (Prunus persica) is an economically important temperate fruit crop due to its edible fruits. Due to the need to develop new varieties better adapted to climate change, it is of great interest to find germplasm adapted to warmer conditions, such as those found in the Canary Islands. Peach was an important crop during the last century in one of those islands (La Palma), but its cultivation has been abandoned in recent years. Currently, commercial production is relict and isolated trees are relegated to fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…These variability levels are similar to those reported in species with high economic and ornamental values, such as cherry Prunus pseudocerasus Lindl. (Chen et al, 2015) and Prunus persica (Pérez et al, 2020). Bantawa et al (2011) found a high level of polymorphism (68.52%) in Gaultheria fragantissima using RAPD.…”
Section: Genetic Diversity Analysismentioning
confidence: 99%
“…These variability levels are similar to those reported in species with high economic and ornamental values, such as cherry Prunus pseudocerasus Lindl. (Chen et al, 2015) and Prunus persica (Pérez et al, 2020). Bantawa et al (2011) found a high level of polymorphism (68.52%) in Gaultheria fragantissima using RAPD.…”
Section: Genetic Diversity Analysismentioning
confidence: 99%
“…In a different study also using SSR markers, Bouhadida et al [11] found results similar to ours, identifying 'Pigat' and 'Rojo Amarillo Septiembre' as genetically close accessions. Our phenotypic records have not shown considerable differences among the three members of the clone group 12 in terms of harvest time and fruit traits, which may indicate that if the genotype differences found by Pérez et al [34] really exist, these changes can occur in noncoding regions and do not influence gene expression and fruit phenotype.…”
Section: Snp Genotyping Identification Of Duplicates and Labeling Errorsmentioning
confidence: 44%
“…Lack of genetic differences among samples could be due to lack of SNPs in the array from specific regions of the peach genome, although the amount of markers used in this study is clearly higher than in previous studies [8]. Some of the clones detected in the present study have been characterized previously with SSRs [11,21,24,26,27,34]. The clone groups detected here (clone groups 1, 2, 4, 5, 6, 7, 8, 10, 13) are in agreement with the genetic proximity observed in previous works, in which small differences in one or two markers, genetically close, were observed.…”
Section: Snp Genotyping Identification Of Duplicates and Labeling Errorsmentioning
confidence: 61%
See 2 more Smart Citations